The Impact of Continuous Virologic Suppression on the Development of Non-AIDS Diagnoses. (4th October 2017) - Joya, Christie; Won, Seunghyun; Deiss, Robert; Okulicz, Jason; O'Bryan, Thomas; Maves, Ryan; Schofield, Christina; Ferguson, Tomas; Whitman, Timothy J; Agan, Brian; Ganesan, Anuradha
Abstract: Background: In the era of effective antiretroviral therapy (ART) non-AIDS diagnoses (NAD) have emerged as significant concerns. HIV viremia is an important driver of systemic inflammation that has been linked to the development of NAD. In this study, we examined the distribution of NAD in a group of early diagnosed and treated HIV-infected individuals with equal access to care to evaluate the effect of continuous virologic suppression (CS) on NAD. Methods: The U.S. Military HIV Natural History Study (NHS) is a prospective cohort of HIV-infected DoD beneficiaries the majority of whom are dated seroconverters. Medical record review and structured interviews are utilized to capture NAD. We included subjects initiating ART after 1996 if they had ≥2 viral loads (VLs) measured while on ART. CS was defined as having all VLs <50 copies/mL. A Cox proportional hazard model was used to evaluate the association between CS and NAD. Results: Of the 2, 642 eligible participants (93% male, 43% African-American AA), median follow-up 6.5 (IQR 3.31–12) years, 985 (37.3%) subjects (94% male, 42% AA, median follow-up 3.74 years) met criteria for CS. The median time from HIV diagnosis to ART initiation was 1.34 (IQR 0.19–5.46) years, while the median seroconversion window was 1.31 (IQR 0.8–2.1) years. A total of 402 (15.2%) NAD were recorded and were recorded (table). Factors associated with NAD included older age at ART initiation (HR 1.6 per 10-year increase [95% CI 1.4–1.8]) and female gender (HR 1.6 [95% CI 1.0–2.7]), while a higher CD4 count was protective (HR 0.93 per 50 cell increase [95% CI 0.90–0.95]). CS status was not associated with NAD (HR 0.75 [95% CI 0.50–1.11]). Conclusion: In the ART era, about 1 in 7 NHS subjects had a NAD. The numbers of NAD in the CS subjects were lower than the rest of the cohort. While not statistically significant, the hazard ratios trended towards demonstrating a benefit for continuous virologic suppression. This trend is consistent with previous reports that have demonstrated a benefit of immunologic reconstitution and virologic control on the incidence of NAD. Disclosures: All authors: No reported disclosures.